Modulus estimates of semirings with applications to boundary extension problems - Golberg, Anatoly; Sugawa, Toshiyuki; Vuorinen, Matti (SPRINGER BASEL AG, 2025)
In our previous paper (Golberg et al. in Comput Methods Funct Theory 20(3-4):539-558, 2020), we proved that the complementary components of a ring domain in Rn\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathbb {R}<^>n$$\end{document} with large enough modulus may be separated by an annular ring domain and applied this result to boundary correspondence problems under quasiconformal mappings. In the present paper, we continue this work and investigate boundary extension problems for a larger class of mappings.